Flora of Yenice Wildlife Development Area (Karabuk/Turkey) - Öztürk Pulatoğlu, Ayşe; Güney, Kerim (Bartın Üniversitesi, 2021)
The study was carried out in Karabük Yenice Wildlife Development Area between 2015-2017 in order to determine the flora of the region. 297 genera and 445 taxa belonging to 83 families growing naturally in the area were identified and 2225 specimens belonging to them were collected. Of these taxa, 6 genera belonging to 5 families and 7 taxa belonging to these genera are from Pteridophyta, 78 families and 438 taxa are from the Spermatophyta division. 4 genera and 6 taxa belong to the Gymnospermae class, while 432 species and infraspesific taxa belonging to 75 families belong to the Angiospermae class. The family with the most taxa in the study area was identified as Asteraceae. This family is followed by Fabaceae, Rosaceae, Poaceae families, respectively. The total number of endemic taxa in the area is 17. According to the Red Book of Plants of Turkey, 2 taxa are classified as NT, 3 taxa EN, 9 taxa LC, 1 taxon VU among endemic taxa. 2 taxa were not evaluated in any category. 2 taxa are under protection by BERN and 17 taxa are under protection by CITES.

Çalışma, bölgenin florasını belirlemek amacıyla 2015-2017 yılları arasında Karabük Yenice Yaban Hayatı Geliştirme Sahası’nda gerçekleştirilmiştir. Alanda doğal olarak yetişen 83 familyaya ait 297 cins ve 445 takson tespit edilmiş ve bunlara ait toplam 2225 örnek toplanmıştır. Bu taksonlardan 5 familyaya ait 6 cins ve bu cinslere ait 7 takson Pteridophyta, 78 familya ve 438 takson ise Spermatophyta şubesindendir. Bunlardan 3 familya, 4 cins ve 6 takson Gymnospermae sınıfına, 75 familyaya ait 432 tür ve tür altı takson ise Angiospermae sınıfına aittir. Araştırma alanında en çok takson içeren familya Asteraceae olarak tespit edilmiştir. Bu familyayı sırasıyla Fabaceae, Rosaceae, Poaceae familyaları takip etmektedir. Alanda toplam endemik takson sayısı 17’dir. Türkiye Bitkileri Kırmızı Kitabı’na göre endemik taksonlar içerisinde 3 takson EN, 1 takson VU, 2 takson NT, 9 takson LC kategorisinde değerlendirilmektedir. 2 takson ise herhangi bir kategoride değerlendirilmemiştir. 2 takson BERN, 17 takson ise CITES tarafından koruma altında bulunmaktadır.
Keywords: Forest Industry Engineering; Flora; Yenice YHGS; Karabük; Turkey; Flora; Yenice YHGS; Karabük; Türkiye; Orman Endüstri Mühendisliği